2004
DOI: 10.1007/s00419-004-0329-6
|View full text |Cite
|
Sign up to set email alerts
|

Modal parameter estimation based on the wavelet transform of output data

Abstract: The paper presents the results of the research on modal parameter estimation based alone on output measurements. A system is excited randomly and random decrement functions are used to separate the random responses from the determination free vibrations. It is shown that on estimation of the natural frequencies and damping ratios of the system is possible using the wavelet transform of the system's free response. A particular form of the son wavelet function improves the results compared to those obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 5 publications
0
24
0
1
Order By: Relevance
“…(10) is always smaller than 1.2 Â 10 À 3 . Moreover, recent studies of mechanical fault detection, impact and singularity detection have used the Morlet function, (see Ruzzene et al, 1997;Staszewski, 1997;Jordan et al, 1998;Hajj et al, 1998;Weggel et al, 1999;Kelley et al, 2000;Teisseire et al, 2000;Patsias and Staszewski, 2002;Lardies et al, 2004;Liu and Babanin, 2004;Ren, 2004 andTse, 2005).…”
Section: Mother Wavelet Selectionmentioning
confidence: 98%
See 1 more Smart Citation
“…(10) is always smaller than 1.2 Â 10 À 3 . Moreover, recent studies of mechanical fault detection, impact and singularity detection have used the Morlet function, (see Ruzzene et al, 1997;Staszewski, 1997;Jordan et al, 1998;Hajj et al, 1998;Weggel et al, 1999;Kelley et al, 2000;Teisseire et al, 2000;Patsias and Staszewski, 2002;Lardies et al, 2004;Liu and Babanin, 2004;Ren, 2004 andTse, 2005).…”
Section: Mother Wavelet Selectionmentioning
confidence: 98%
“…Using asymptotic techniques, (see Delprat et al, 1992;Carmona et al, 1997;Staszewski, 1997;Ruzzene et al, 1997;Brenner and Lind, 1998;Piombo et al, 2000;Boltezar, 2004;Lardies et al, 2004;Yan et al, 2006a;Meo et al, 2006;Erlicher andArgoul, 2007 andTan et al, 2008), the wavelet transform can be expressed approximately as:…”
Section: Modal Parameters Identificationmentioning
confidence: 99%
“…It has seen a surge of such activities in the last decade. The most extensively employed techniques involve the short-time Fourier transform (STFT), WignerVille distribution (WVD), wavelet transform, and Hilbert-Huang transform (HHT) and their enhanced derivatives [2][3][4][5] . However, the non-parametric T-F methods suffer from various limitations respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the time domain [7][8][9][10] correlation functions or covariance matrices between output responses are used to obtain a companion matrix or a transition matrix and extract modal parameters from eigen decomposition of these matrices. In the time-frequency domain [11,12] the wavelet transform of the free response of the structure is used. The wavelet transform of a signal results in a complex valued form and it is shown that the modulus of the wavelet transform is related to damping ratios and its phase to eigenfrequencies.…”
Section: Introductionmentioning
confidence: 99%